2022
DOI: 10.1097/yct.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in Children and Adolescents in Germany—A Case Series From 3 University Hospitals

Abstract: ObjectiveElectroconvulsive therapy (ECT) is a well-established, safe, and efficacious treatment for severe psychiatric disorders. In children and adolescents, it is used much less frequently than in adults, likely because of a lack of knowledge.MethodsWe retrospectively analyzed all patients aged 12 to 17 years who completed a course of ECT at 3 psychiatric university hospitals in Germany between 2010 and 2020. Clinical Global Impression Severity (CGI-S) scores were assessed based on electronic medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Abrams (48) stated, "ECT as a procedure is ethical", and he also stated, "that the response to ECT in children … is no different from that obtained in adults: excellent". There are studies reported the use of ECT on children for many reasons like mental issues, bad behaviours, disorders, and mood disorders (49)(50)(51)(52)(53) which confirms that an electric shock is ethically acceptable. Considering that ECT uses voltage ranging from 70 to 120 volts (32), while the current patent uses only 2-4 voltage.…”
Section: Discussionmentioning
confidence: 78%
“…Abrams (48) stated, "ECT as a procedure is ethical", and he also stated, "that the response to ECT in children … is no different from that obtained in adults: excellent". There are studies reported the use of ECT on children for many reasons like mental issues, bad behaviours, disorders, and mood disorders (49)(50)(51)(52)(53) which confirms that an electric shock is ethically acceptable. Considering that ECT uses voltage ranging from 70 to 120 volts (32), while the current patent uses only 2-4 voltage.…”
Section: Discussionmentioning
confidence: 78%
“…It was initially used for seizure treatment in children as young as three years of age 29 . Since that time, numerous studies support the safety and efficacy of pediatric ECT for depression, psychosis, and catatonia 30-34 . Despite these encouraging findings, however, it is estimated that 0.03% of youth hospitalizations involved the administration of ECT, suggesting that it is rarely utilized for pediatric patients 35 .…”
Section: Questions To the Consultantsmentioning
confidence: 99%
“…29 Since that time, numerous studies support the safety and efficacy of pediatric ECT for depression, psychosis, and catatonia. [30][31][32][33][34] Despite these encouraging findings, however, it is estimated that 0.03% of youth hospitalizations involved the administration of ECT, suggesting that it is rarely utilized for pediatric patients. 35 Administration in pediatric populations is likely limited by stigma, minimal education in psychiatric training programs, provider comfort, and access.…”
Section: Questions To the Consultantsmentioning
confidence: 99%
“…In parallel, this issue of the journal describes recommended guidelines for the pre-ECT evaluation 2 . We also present 2 articles on the use of ECT in vey psychiatrically ill adolescents, finding that young patients respond well to ECT, 3 but those adolescents with catatonia are often not offered this effective treatment 4 . At the other end of the age spectrum, we learn that nonresponse to ECT in depressed older people may still be followed by remission to other treatments in 24.5% of cases of nonresponse over the subsequent 2 years 5 .…”
mentioning
confidence: 99%